2011
DOI: 10.1002/ibd.21493
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric modification of the Montreal classification for inflammatory bowel disease

Abstract: These modifications are termed the Paris Classification. By adhering to the Montreal framework, we have not jeopardized or altered the ability to use this classification for adult onset disease or by adult gastroenterologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
978
0
34

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,297 publications
(1,022 citation statements)
references
References 64 publications
10
978
0
34
Order By: Relevance
“…The population was therefore stratified by 10-year age groups as previously described. 3,4 As far as disease location, we agree that the classification of ileal lesions with caecal involvement as L3 may have led to an overestimation of the number of cases of L3 disease when compared with other studies. Nevertheless, as this classification was applied during the whole study period, it did not influence the increase in extensive disease we reported.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…The population was therefore stratified by 10-year age groups as previously described. 3,4 As far as disease location, we agree that the classification of ileal lesions with caecal involvement as L3 may have led to an overestimation of the number of cases of L3 disease when compared with other studies. Nevertheless, as this classification was applied during the whole study period, it did not influence the increase in extensive disease we reported.…”
supporting
confidence: 49%
“…First, although the investigators had previously detailed their diagnostic criteria, 2 these are not the universally accepted standards -notably the age-limits used were not those described in either the Montreal 3 or the Paris classification. 4 Secondly, the classification of ileal lesions with caecal involvement as L3 disease rather than L1 make comparisons with other studies difficult, and subsequently limits the impact of the described increase in extensive disease (L3 + L4). It is also not clear whether the reported increase was a result of the 10% rise in 'complete gut investigation' or to changes in the rate of successful ileal intubation.…”
Section: The Changing Epidemiology Of Paediatric Inflammatory Bowel Dmentioning
confidence: 99%
“…The disease activity of Crohn disease (CD) and ulcerative colitis (UC) was assessed using the pediatric Crohn's disease activity index and pediatric ulcerative colitis activity index, respectively. The disease phenotype at diagnosis was categorized according to the Paris classification (6). Hypergammaglobulinemia was defined as IgG levels of ≥1470 mg/dL for children aged <10 years, ≥1560 mg/dL for those aged 10-14 years, and ≥1600 mg/dL for those aged >14 years.…”
Section: Description Of Variablesmentioning
confidence: 99%
“…Infection with tuberculosis was excluded using the Mantoux and QuantiFERON-TB-Gold-Test in tube ® (Cellestis Ltd; Carnegie, VIC, Australia) tests prior to starting treatment. Disease phenotype was determined according to the Paris classification (24), disease activity using the Pediatric Crohn's Disease Activity Index (PCDAI) (25,26) and the degree of mucosa inflammation by fecal calprotectin (FC, Calprest ® , Eurospital, Trieste, Italy). The PCDAI index and FC were determined at week 12 and thereafter repeated at each subsequent visit.…”
Section: Methodsmentioning
confidence: 99%